Uncommon Location of Purpura Fulminans: Case Report and Literature Review - Sahar Hasan Alsharif; Abdullah Al-Omair; Fedaa Andijani (Karger Publishers, 2020)
Purpura fulminans is a critical, mostly fatal, thrombotic syndrome that requires urgent intervention. Purpura fulminans is an acute purpuric rash characterized by coagulation of the microvasculature, which leads to purpuric lesions and skin necrosis. In this report, we present a rare case of an adult patient who was admitted with rapidly forming purpura fulminans in an uncommon location.